2018
DOI: 10.1177/0266666918765907
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the adoption of e-learning technologies among higher education students in Nigeria

Abstract: The aim of the study is to investigate factors that influence the adoption and use of educational technology by students of a higher education institution in developing countries. The study employed the unified theory of acceptance and use of technology (UTAUT). The online survey method was used to collect data from 286 students of a higher education institution in Nigeria. The maximum likelihood method based on structural equation modelling (SEM) using IBM Amos 22.0 application was used to analyse the data. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
101
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(138 citation statements)
references
References 40 publications
9
101
1
2
Order By: Relevance
“…So far there has been very little research carried out to understand the factors responsible for students' adoption of eLearning in Nigeria, and this could be due to the relatively small number of higher education institutions that have the facilities and resources to implement eLearning. One notable study on the acceptance of eLearning in a Nigerian University was done by Yakubu and Dasuki (2018). The research employed the UTAUT framework to investigate the factors responsible for influencing the students' usage of the Canvas learning management system (LMS).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…So far there has been very little research carried out to understand the factors responsible for students' adoption of eLearning in Nigeria, and this could be due to the relatively small number of higher education institutions that have the facilities and resources to implement eLearning. One notable study on the acceptance of eLearning in a Nigerian University was done by Yakubu and Dasuki (2018). The research employed the UTAUT framework to investigate the factors responsible for influencing the students' usage of the Canvas learning management system (LMS).…”
Section: Introductionmentioning
confidence: 99%
“…These four constructs were responsible for influencing use behavior through behavioral intentions. Yakubu and Dasuki (2018) called for further research using other frameworks to investigate Nigerian students' acceptance of eLearning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The modern technology especially the Internet has transformed education that was once limited within four walls. This shift from traditional method to use of technology mediated tools is referred to as electronic learning (e-learning) (Yakubu and Dasuki, 2018). E-learning technologies have given education field a paradigm shift from teacher-centered to learner-centered (Oye et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…E-learning technologies have given education field a paradigm shift from teacher-centered to learner-centered (Oye et al, 2014). Past studies demonstrated that anywhere and anytime learning and access to information and communication are facilitated through e-learning (Peña-Ayala et al, 2014;Nurakun et al, 2018;Yakubu and Dasuki, 2018).…”
Section: Introductionmentioning
confidence: 99%